PENGEMBANGAN SISTEM HUKUM DALAM ERA OTONOMI (Strategi Pembangunan Hukum dan Substansi Sistem Hukum Daerah) - Kotan Y Stefanus (Masalah-Masalah Hukum, 2010)
Local legal system in Indonesia had been grey potret and become a servant of power. So, we must develop prograsive-alternative legal development strategy, that is empowerment of all society components to express their need while push low strafication collective group to influence decison making and consistenly improve legislative product. This effort should be follow by globalization local values anoved dlocalization global values. Integration of those efforts become a order that is known as local legal system.Kata Kunci : Sistem hukum daerah, strategi pembangunan hukum. penegakkan hukum, politik hukum.